A new relationship for calculating the exponential integral used for constant-terminal-rate solution of diffusivity equation - Gomaa, Sayed (IJRDO -JOURNAL OF MATHEMATICS, 2016)
The constant-terminal-rate solution of diffusivity equation is an integral part of most transient test analysis techniques, such as with drawdown and pressure buildup analyses. Most of these tests involve producing the well at a constant flow rate and recording the flowing pressure as a function of time. There are two commonly used forms of the constant-terminal-rate solution: the